An examination of the effects of consumer racism and consumer ethnocentrism on willingness to buy products associated with ethnic Chinese - Abdul Latif, Samshul Amry; Abdul Talib, Asmat Nizam (Australia New Zealand International Business Academy (ANZIBA) Conference 2015, 2015)
Purpose –this paper attempts to investigate the effects of consumer racism and ethnic-level consumer ethnocentrism on Malay consumers’ willingness to buy toward products associated with Malaysian ethnic Chinese.